Development of internal audit in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
At the present stage requirements to increase of effective management of the enterprise which cause need of functional activization and reforming of internal control as a component of management increase. At implementation of business activity in the organizations the difficult economic mechanism with many independent and interacting systems operates. Such systems are the account and internal control. These systems in the organizations unite not only with the general target orientation as functions of management, but also realization stages: preparation of economic information on an economic entity, its analysis and an assessment, correction of mistakes with participation of services of internal audit. Development of the organizations acting as owners of means of production and products of work in many respects depends on safety of these means and efficiency of their use. Features of internal audit of the enterprises are caused by their difficult organizational structure, territorial remoteness of branches, big specific weight of fixed assets in assets.
Keywords: audit; audit and analysis; analitical prizedure.